Device-assisted intravesical chemotherapy treatment for nonmuscle invasive bladder cancer: 2022 update. Issue 5 (24th September 2022) - Vartolomei, Mihai Dorin; Ferro, Matteo; Roth, Beat; Teoh, Jeremy Yuen-Chun; Gontero, Paolo; Shariat, Shahrokh F.
Abstract : Purpose of review: To critically analyze the oncological outcomes and safety profile of device-assisted intravesical chemotherapy studies reported in 2021. Studies were considered eligible if they included patients with nonmuscle invasive blood cancer (NMIBC), had a prospective or retrospective design, included at least 10 patients, were published in 2021, and assessed the oncological impact of device-assisted intravesical chemotherapy and/or reported standardized adverse effects (AEs). Recent findings: Eight new studies reported oncological outcomes after hyperthermic intravesical chemotherapy (HIVEC). In Bacillus Calmette-Guérin (BCG) naive patients, the reported 2-yr. recurrence-free survival (RFS) ranged from 70.7% to 82.4%, with one study reporting 2 yr. progression free survival (PFS) of 92%. In both BCG naive and BCG refractory patients, the reported 1-yr. RFS ranged from 60.5% to 70% and PFS was 94% in one study. For radiofrequency-induced HIVEC, the reported 5-yr. estimates were 38%for RFS and 91.5%for PFS. Regarding AEs, 10.2% of patients had severe AEs. Six studies reported AEs after HIVEC; the majorities were grade 1–2 AEs. Summary: Data coming from the studies published in the last years provides support for a consolidating role of device-assisted intravesical chemotherapy as a safe and effective alternative first- or second-line adjuvant treatment of patients with NMIBC.